Comparative Effectiveness of Rituximab and Common Induction Therapies for Lupus Nephritis: A Systematic Review and Network Meta-Analysis - Li, Kang; Yu, Yanqiu; Gao, Yuan; Zhao, Fei; Liang, Zheng; Gao, Junjie (Frontiers in Immunology, 2022)
Objective This study aimed to compare the efficacy and safety (infection events) between rituximab (RTX), tacrolimus (TAC), mycophenolate mofetil (MMF), and cyclophosphamide (CYC) as induction therapies in lupus nephritis (LN). Methods Electronic databases, including PubMed, EMBASE, and the Cochrane Library, were searched from inception up to December 9, 2021. Bayesian network meta-analysis was used to combine the direct and indirect evidence of different drugs for LN patients. The pooled relative effects were shown using odds ratios (ORs) and 95% credible intervals (CrIs). Results Nineteen studies (1,566 patients) met the inclusion criteria and were selected in the present study. The network meta-analysis reported that no statistically significant differences were found in partial remission (PR) and infection among the four drugs. RTX showed a significantly higher complete remission (CR) than MMF (OR = 2.60, 95% CrI = 1.00–7.10) and seemed to be more effective than CYC (OR = 4.20, 95% CrI = 1.70–14.00). MMF had a better CR than CYC (OR = 1.60, 95% CrI = 1.00–3.20). TAC presented a better overall response than CYC (OR = 3.70, 95% CrI = 1.20–12.00). Regarding CR and overall response, the maximum surface under the cumulative ranking curve (SUCRA) values were 96.94% for RTX and 80.15% for TAC. The maximum SUCRA value of infection reaction was 74.98% for RTX and the minimum value was 30.17% for TAC, respectively. Conclusions RTX and TAC were the most effective drugs for induction remission in LN. Among the four drugs, TAC had the lowest probability of infection, and RTX showed the highest probability of experiencing an infection. This meta-analysis could not conclude about other adverse events.